A comparative study of free-hand fine needle aspiration cytology and ultrasound guided fi ne needle aspiration cytology in the diagnosis of thyroid swellings at BP Koirala Institute of Health Sciences- a tertiary care centre in Nepal - Agarwal, M; Sinha, A K; Agrawal, C S; Bhandary, S; Tiwari, A; Agarwal, R K (Health Renaissance, 2015)
Background: Thyroid lesions are commonly encountered in clinical practice and it is mandatory to know and record the nature of pathology prior to definitive therapy. Fine needle aspiration cytology (FNAC) is a time tested, cheap, reliable and safe method to establish a cytological diagnosis of the nature of the disease. Ultrasound guided FNAC has the potential to reduce inadequacy rates and is regarded as the optimal cytological method for diagnosis. Objective: To compare the results of free-hand and ultrasound-guided FNAC of thyroid swellings and to find out the diagnostic reliability of free-hand FNAC and ultrasound-guided FNAC using histological diagnosis as the gold standard. Methods: Fifty-five patients with thyroid swelling who were subjected to free-hand and ultrasound-guided FNACs and who subsequently underwent surgery over one year were studied. Results: Ultrasound guided FNAC results revealed 72.75 % benign lesions and 25.45 % of malignant lesions, and free hand FNAC revealed 52.73 % benign and 16.36% malignant cases. A 14.55 % inadequacy rate was seen in the free hand group. Histological gold standard diagnosis comprised of 60 % benign and 40 % malignant cases. Sensitivity and specificity of free-hand and ultrasound guided FNAC in diagnosing malignancy of the thyroid were 56.25% and 100%; and 63.64% and 96.97% respectively. Conclusion: Free hand FNAC of thyroid swellings is more convenient and cost effective as compared to ultrasound guided FNAC. However, the diagnostic yield in ultrasound guided FNAC is significantly more in terms of accuracy especially in cystic and tiny lesions. Health Renaissance 2014;12(2): pp. 78-86